2020
DOI: 10.3329/bjms.v19i0.47831
|View full text |Cite
|
Sign up to set email alerts
|

“Innovative Anatomy assessment methods in COVID-19 Pandemic: statistical observations and students viewpoints”

Abstract: Background: Currently anatomy training and assessment is seriously disrupted in COVID-19 Pandemic lockdown. New challenges of anatomy curriculum and assessment method development are being attempted based upon resources, expertise and technical skills of educators. This study aims at creating a standard operation procedure (SOP) for conducting gross anatomy assessment, finding statistical relevance and discusses viewpoints of students reflected in feedback. Materials and methods: a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Even though anatomy educators modified the setting and the materials of the practical examinations, the assessment format predominately remained the same, which illustrates their adaptability. Though the present study found image‐based, online practical examinations were preferred during Covid‐19, researchers have demonstrated the feasibility of conducting oral anatomy examinations using telephones and video conferencing software (Gupta et al, 2020; Byrnes et al, 2021). Online, image‐based practical examinations were also a strategy for anatomy educators that published data about Covid‐19‐related institutional and curricular changes (Longhurst et al, 2020; Herr and Nelson, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…Even though anatomy educators modified the setting and the materials of the practical examinations, the assessment format predominately remained the same, which illustrates their adaptability. Though the present study found image‐based, online practical examinations were preferred during Covid‐19, researchers have demonstrated the feasibility of conducting oral anatomy examinations using telephones and video conferencing software (Gupta et al, 2020; Byrnes et al, 2021). Online, image‐based practical examinations were also a strategy for anatomy educators that published data about Covid‐19‐related institutional and curricular changes (Longhurst et al, 2020; Herr and Nelson, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…20 The achievement of learning outcome at the end of any effective learning strategies at the end of the course that the learner accomplished is an important milestone in education. 21,22 Hence how video-based lecture affects the different domains of learning outcome is being evaluated in the present study. In the present study we compared the achievements of different domains of learning outcome between traditional lecture and video-based lecture.…”
Section: More Information and Difficultmentioning
confidence: 99%
“…4 Pre-clinical medical students face challenges as the face-to-face teaching and other hands-on training such as cadaveric dissections, practical sessions using physical aids such as bones, specimens, and models and laboratory classes cannot take place. [5][6][7][8] However, continuity of medical education is crucial to prepare future medical graduates. Therefore, the COVID-19 pandemic has now forced educators around the world to shift from face-to-face teaching to online teaching.…”
mentioning
confidence: 99%
“…22 There are also reports of lack of student engagement due to attention deficit, multitasking during attending sessions, poor audio and video quality, internet issues, etc., and it is also difficult to conduct a secure and valid online assessment. 8 For the transformation to online teaching-learning, Reyna (2020) 23 has provided few guidelines for the faculties. It is suggested to engage students as partners in the learning process, use weekly video vignettes to create online teacher presence by describing the learning outcomes of the week, and inform how students will learn.…”
mentioning
confidence: 99%
See 1 more Smart Citation